Information about bank risk in options prices - Swidler, Steve; Wilcox, James A. (Journal of Banking & Finance, 2002)
The volatility of its share price reflects the volatility of the market value of a bank's assets. We present data for the volatilities of individual banks' shares that are implied by the prices of options on the banks' shares. We present evidence that implied volatilities (IV's) better forecast actual, future volatilities of share prices than historical volatilities do. Banks' IV's are correlated with marketwide volatility, with the levels of their own share prices, with their own subordinated debt yield spreads, and with other banks' IV's. Bank capital reduces the response of IV's to market volatility. IV's are likely to add information about bank risk that is timely, cheap, objective, and useful.